2016
DOI: 10.1016/j.celrep.2016.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of G9a Regulates Neuronal Differentiation

Abstract: Chromatin modifications are critical for the establishment and maintenance of differentiation programs. G9a, the enzyme responsible for histone H3 lysine 9 dimethylation in mammalian euchromatin, exists as two isoforms with differential inclusion of exon 10 (E10) through alternative splicing. We find that the G9a methyltransferase is required for differentiation of the mouse neuronal cell line N2a and that E10 inclusion increases during neuronal differentiation of cultured cells, as well as in the developing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 62 publications
1
67
1
Order By: Relevance
“…Multiple splice variants have been noted both in the human and mouse, denoted by inclusion/exclusion of a 5 0 exon, as well as inclusion/exclusion of exon 10. [53][54][55][56] Although none of these splice variants has been reported to effect the overall HMT function of the Ehmt1/2 dimer, both alternatively spliced 5 0 domain and exon 10 have independently been reported to be required for nuclear localization. 54,56 Furthermore, activation by the human EHMT2 protein has been found to be predominantly dependent of the hEHMT2-s variant which lacks part of the 5 0 TAD, in at least some contexts.…”
Section: Methylation-independent Transcriptional Activating Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple splice variants have been noted both in the human and mouse, denoted by inclusion/exclusion of a 5 0 exon, as well as inclusion/exclusion of exon 10. [53][54][55][56] Although none of these splice variants has been reported to effect the overall HMT function of the Ehmt1/2 dimer, both alternatively spliced 5 0 domain and exon 10 have independently been reported to be required for nuclear localization. 54,56 Furthermore, activation by the human EHMT2 protein has been found to be predominantly dependent of the hEHMT2-s variant which lacks part of the 5 0 TAD, in at least some contexts.…”
Section: Methylation-independent Transcriptional Activating Functionsmentioning
confidence: 99%
“…[53][54][55][56] Although none of these splice variants has been reported to effect the overall HMT function of the Ehmt1/2 dimer, both alternatively spliced 5 0 domain and exon 10 have independently been reported to be required for nuclear localization. 54,56 Furthermore, activation by the human EHMT2 protein has been found to be predominantly dependent of the hEHMT2-s variant which lacks part of the 5 0 TAD, in at least some contexts. 53 It is therefore possible that alternative splicing the Ehmt2 transcript acts to balance both activator and repressor, as well as nuclear versus cytoplasmic functions.…”
Section: Methylation-independent Transcriptional Activating Functionsmentioning
confidence: 99%
“…JHDMs, which belong to the superfamily of 2-oxoglutarate and Fe 2+ -dependent dioxygenases, hydroxylate the methyl group in a lysine residue of histones, and in turn the oxidized methyl is released as formaldehyde (50) not been demonstrated, it was reported that substantial amounts of G9a and its splicing variant are present in the cytoplasm (52). In addition, a proteomic analysis revealed that many non-histone proteins in the cytoplasm are methylated by G9a/GLP (53), which indirectly supports the cytoplasmic location of G9a/GLP.…”
mentioning
confidence: 99%
“…Interestingly, another histone methyl transferase, G9a, that is specific for dimethylation of H3K9 has recently been shown to participate in an alternative splicing positive loop that enhances neuron differentiation (18). It is now more evident that when studying the molecular bases of cancer, the view should not be restricted to transcriptional regulation or to epigenetic alterations at the promoter and regulatory regions of genes.…”
Section: Discussionmentioning
confidence: 99%